Glossary of terms content words as used in food and beverage services (FBS) NC II assessment scripts of Oton National high School grade 12 FB1 NCII learners - Villanueva, Aivon T (2018.)
One hundred thirty-five (135) Food and Beverage Services NC II Assessment Scripts of Grade 12 Technical Vocational Livelihood (TVL) learners specializing in Food and Beverages Services (FBS) NC II were examined to come up with the glossary of terms used by FBS NC II learners of Oton National High School for the school year 2017-2018. The script has nine parts: (1) Preparing dining area and Cleaning and checking the table, (2) Preparing and setting up the table, (3) Welcoming and seating the guest, (4) Taking and Processing order, (5) Serving food orders, (6) Providing room service, (7) Setting up trays and trolleys, (8) Presenting and serve food and beverage order to guests, (9) Clearing room service equipment. These are based on the competencies which must be learned in the Food and Beverages Services (FBS) area of specialization in the Technical Vocational Livelihood (TVL) Track. Content words and their usage in the assessment were considered, resulting in a glossary of common terms used by the learners, which contain words and expressions that are inappropriately or incorrectly used. While the glossary could add to the vocabulary reservoir used in the field of Food and Beverage Services as offered in the Senior High School curriculum, they reflect the learners? inadequate or unsuccessful transfer of the knowledge in the production level. The study points out the need for teachers of language and of specialized areas to coordinate towards integrated and effective language use.
Special Problem (Master of Education in English as a Second Language)Division pf Professional Education, College of Arts and Sciences
Keywords: Food and Beverage Services (FBS) NC II script assessment -- Research